Assessment of Antioxidant Activity of Nigella sativa seed: An In Vitro Approach - Narender Boggula,; Manasa Reddy Narayana Reddy Gari,; Chaitanya Kallu,; Naresh Vallakati, (Asian Journal of Pharmaceutical Research and Development, 2025)
Medicinal plants, vegetables, and food products are rich sources of natural compounds that may play an important role in human health, by maintaining it, or preventing and curing diseases. In medicinal plants, these compounds are considered as bioactive natural compounds that can be subsequently developed as new drugs.Nigella sativa (N. sativa) (Family Ranunculaceae) is a widely used medicinal plant throughout the world. It is very popular in various traditional systems of medicine like Unani and Tibb, Ayurveda and Siddha.The aim of the present research is to assess the anti-oxidant activity of selected Nigella sativa plant seeds ethanolic extract.Ethanol was used to extract the plant powder three times using a Soxhlet apparatus. The anti-oxidant activity estimated by DPPH, ABTS, and H2O2 radicals scavenging assays.The IC50 values were determined by NSSE and ascorbic acid to be 192.25mL-1 (Y= 0.217x+1.028) and 185.65μg mL-1 (Y= 0.2332x+7.61).Results revealed that the pomegranate can be categorized as a leave with extremely high anti-oxidant potential.These bioactive substances could have extra nutritional properties and a central role in diet disease relationships. Further studies are required to disclose possible new bioactive constituents of the unsaponifiable fraction.